Transformerless Power Converter For Grid-Connected PV System With No-Ripple Input Current And Low Ground-Leakage Current - Azri, Maaspaliza; Abd.Rahim, Nasrudin (Institution of Engineering and Technology, 2014)

(untitled)
The application of boost converters is highly favored in PV module integrated converter (MIC) systems.The conventional boost converter operating in continuous inductor-current mode (CICM),however,has a pulsating, high-ripple input current,which causes power loss and decreases the energy flowing from non-linear sources like the PV panel.Therefore,this paper proposes a new modified boost converter that has a no-ripple input current.The proposed converter uses a series of input inductance to produce zero-ripple input current during continuous inductor-current mode,without any LC or C filter elements.It is capable of high power-conversion efficiency for the whole system without the use of any transformer or galvanic isolation components.In addition, this proposed boost converter is integrated with an H-Bridge inverter for a transformerless PV grid-connected system.The issue of electrical safety of the high ground-leakage current (due to the parasitic capacitance of the PV panel and frame and lack of galvanic isolation) is resolved by bipolar SPWM technique in the H-Bridge inverter,without any additional hardware.The proposed DC-AC transformerless inverter grid-connected PV system, which has a new modified boost converter and bipolar H-Bridge inverter,is verified by a 1-kW hardware prototype simulated and validated by experiment.The results show zero-ripple input current,high power-conversion efficiency,near-unity power factor,low current-THD,and low ground-leakage current.